Reflexiones jurídicas sobre la protección de datos y el derecho a la intimidad en la autodeterminación informativa (Tema Central) - Villalba Fiallos, Andrea (2017)
The investigation has the objective to establish the legal aspects regarding the right to privacy and its connection with data protection, in order to determine the importance of building public policies and legislative actions that can generate a ponderous balance of rights and a consolidation of basic elements of data protection. The analysis begins with a brief introduction regarding the right to privacy and other related rights, and afterwards attends the supposed absolute character of the fundamental right to privacy. In the next part, the constitutive elements will be developed, making emphasis on the phase of transference of information established in regard to the control of information and delivered to a third party. Finally, the analysis focuses in the study of the relevance of the authorization or valid consent, and in determining the link to the violation of the right to personal data protection and the consequent infringement of personal data by new technologies.